Tracing Creative Thinking Patterns in Homogeneous Primary Student Groups during Collaborative Problem Posing - Febriarsita Eka Sasmita; Wiryanto Wiryanto; Aslam Khan (EduStream: Jurnal Pendidikan Dasar, 2025)
Creative thinking is a vital ability that should be nurtured from the primary level, particularly through collaborative learning activities that engage students in mathematical problem posing. This study aims to investigate the patterns of creative thinking exhibited by primary school students working in homogeneous ability groups during collaborative problem-posing tasks. A qualitative descriptive approach was employed, with data collected through classroom observations, field notes, student-generated problem artifacts, and focus group discussions involving six fifth-grade student groups categorized as high-, medium-, and low-ability. The findings reveal distinct creative thinking patterns across ability groups shaped by internal group dynamics. High-ability groups demonstrated strong fluency in generating ideas but showed limited flexibility and novelty due to dominance by one or two members. Medium-ability groups exhibited more balanced participation, resulting in relatively stronger fluency and flexibility, though originality remained moderate. In contrast, low-ability groups displayed minimal indicators of creative thinking, characterized by passive participation and limited engagement. These results highlight a gap between students’ cognitive potential and their collaborative creative performance within homogeneous group settings. The study concludes that creative thinking in homogeneous ability groups is influenced not only by cognitive level but also by the quality of interaction and equitable participation, underscoring the crucial role of teacher facilitation in designing instructional supports that foster inclusive dialogue and creative collaboration.